2019
DOI: 10.3171/2018.4.jns172596
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment results between 3- and 2-stage Gamma Knife radiosurgery for large brain metastases: a retrospective multi-institutional study

Abstract: OBJECTIVE In order to obtain better local tumor control for large (i.e., > 3 cm in diameter or > 10 cm in volume) brain metastases (BMs), 3-stage and 2-stage Gamma Knife surgery (GKS) procedures, rather than a palliative dose of stereotactic radiosurgery, have been proposed. Here, authors conducted a retrospective multi-institutional study to compare treatment results between 3-stage and 2-stage GKS for large BMs. METHODS This retrospective multi-institutional study involved 335 patients from 19 Gamma Knife fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 50 publications
0
37
0
1
Order By: Relevance
“…Due to the lack of relevant data, pulmonologists or neurosurgeons help patients make informed decisions to select their treatment modality depending on the patients' preference. For patients with relatively larger lesion (≥10 cm 3 ) who are not candidate for surgery, the two-session SRS would be offered as an option (14). For patients with the desire for home care, SRS would also be an option because SRS is a one-day treatment while WBRT takes over 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the lack of relevant data, pulmonologists or neurosurgeons help patients make informed decisions to select their treatment modality depending on the patients' preference. For patients with relatively larger lesion (≥10 cm 3 ) who are not candidate for surgery, the two-session SRS would be offered as an option (14). For patients with the desire for home care, SRS would also be an option because SRS is a one-day treatment while WBRT takes over 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Between the two stages, a biopsy of the cecal lesion, detected by abdomen CT scan, was performed and histopathologic diagnosis of colon adenocarcinoma was made. We chose to treat a cluster of 9 patients, whose greater lesion exceeded 10 cm 3 , with 2-stage modality GKRS (12 Gy to total volume in two sessions, 4 weeks apart) rather than palliative GKRS to minimize tumour recurrence and radiation necrosis [12]. Five of these patients underwent the second stage of their treatment in the time span described in this article (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At present, SRS and SRT are considered key treatments for metastatic brain tumors [1,2,3]. Several patients with fewer than 5 or 10 brain metastases have been successfully treated using radiosurgery [2].…”
Section: Discussionmentioning
confidence: 99%
“…With the aid of stereotactic radiosurgery (SRS), current studies have demonstrated that the presence of fewer than five brain metastasis is associated with excellent tumor control. Moreover, a few reports have concluded that radiosurgery for fewer than 10 brain metastases is not inferior to radiosurgery for fewer than five brain metastases in terms of tumor control [1,2]. However, the treatment of more than 10 brain metastases seems to be more difficult and challenging.…”
Section: Introductionmentioning
confidence: 99%